Beautiful Teams: Insprring and Cautionary Tales from VeternTeam Leaders. - Andrew Stellman [ Editor ] (O'Reilly Media, 2009)
What's it like to work on a great software development team facing an impossible problem? How do you build an effective team? Beautiful Teams takes you behind the scenes with some of the most interesting teams in software engineering history. You'll learn from veteran team leaders' successes and failures, told through a series of engaging personal stories -- and interviews -- by leading programmers, architects, project managers, and thought leaders.